PENGARUH PROFITABILITAS DAN REPUTASI AUDITOR TERHADAP AUDIT DELAY - Maghfur, Afza Nuzhat; Hastuti, Rini Tri (Jurnal Paradigma Akuntansi, 2025)
This study aims to examine the effect of auditor’s reputation, and profitability on audit delay. The population in this study are audited financial reports on food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2021-2022. Sampling was carried out using purposive sampling technique with a total sample of 36 companies over a period of 2 consecutive observations so that the total sample was 120. The data of this study were processed using SPSS version 25.